2021
DOI: 10.1159/000515929
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Antioxidant Effects of Riparin I in a Model of Depression Induced by Corticosterone in Female Mice

Abstract: <b><i>Background:</i></b> Depression is a common, chronic, and often recurrent serious mood disorder. Conventional antidepressants present limitations that stimulate the search for new drugs. Antioxidant and neuroprotective substances are potential antidepressant agents. In this context, riparin I (RIP I) has presented promising results, emerging as a potential source of a new therapeutic drug. In this study, the antidepressant effect of RIP I was evaluated in an animal model of depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Previous studies, using acute and chronic models of stress by repeated administration of corticosterone, have already demonstrated the ability of RIP I and RIP II to decrease the immobility time in forced swimming test, which proves their antidepressant activity (Teixeira et al, 2013;de Sousa et al, 2014;Lopes et al, 2018;Maia Oliveira et al, 2021). Additionally, in the present study, after exposure to various stressors in the CUMS, which is known to affect several brain circuits, resulting in the animal's immobility behavior (Nollet, 2021), RIP I and RIP II showed the ability to reverse the despair-like behavior caused by CUMS.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previous studies, using acute and chronic models of stress by repeated administration of corticosterone, have already demonstrated the ability of RIP I and RIP II to decrease the immobility time in forced swimming test, which proves their antidepressant activity (Teixeira et al, 2013;de Sousa et al, 2014;Lopes et al, 2018;Maia Oliveira et al, 2021). Additionally, in the present study, after exposure to various stressors in the CUMS, which is known to affect several brain circuits, resulting in the animal's immobility behavior (Nollet, 2021), RIP I and RIP II showed the ability to reverse the despair-like behavior caused by CUMS.…”
Section: Discussionmentioning
confidence: 79%
“…In previous studies from our group using acute animal models, RIP I and RIP II showed antidepressant and anxiolytic activities and the mechanism may be related to noradrenergic (α1 and α2 receptors), serotonergic (5-HT2A/2C receptor), and dopaminergic (D1 and D2 receptors) systems (de Sousa et al, 2005(de Sousa et al, , 2007(de Sousa et al, , 2014Teixeira et al, 2013). Furthermore, these molecules showed restorative properties on brain-derived neurotrophic factor (BDNF) levels, in addition to reducing oxidative stress damage in a model of depression induced by repeated administration of corticosterone in mice (Lopes et al, 2018;Maia Oliveira et al, 2021). In this study, we advance the model used to induce depression and cognitive impairments, more closely imitating what occurs in humans, employing a stress model with external factors rather than synthetic hormones (Antoniuk et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated the association between BBB disruption based on changes in the TJ proteins of the cerebral vascular endothelium and the development of psychiatric disorders, with claudin-5 and -12 being considered as the main targets [ 14 , 15 ]. Glucocorticoid treatment is known to induce depressive behavior in mice [ 26 , 27 , 28 ]. In this study, the administration of prednisolone caused decreased locomotor activity and anxiety-like and depression-like behavior; intriguingly, this occurred without changes in the expression of claudin-5 and -12.…”
Section: Discussionmentioning
confidence: 99%
“…All behavioral observations revealed significant changes in accordance with the effects of the application (vehicle) and prednisolone, respectively. The behavioral changes in the conditions of intraperitoneal administration of prednisolone (70 mg/kg) for 7 days (Figure 2) were also characteristic of the systemic action of glucocorticoids [26][27][28]. Although the subsequent molecular analyses focused on approaches with intramuscular injection, this subset was chosen to exclude any peripheral muscular effects during the behavioral analyses.…”
Section: Physiological Effects Of Prednisolone Administrationmentioning
confidence: 99%
“…In addition, the hypothalamic-pituitary-adrenal (HPA) axis plays an important role in the regulation of cortisol, and it is also found that changes in HPA axis with increased amount of plasma cortisol is one of the biological features in severe depression patients (Keller et al, 2017;Malhi and Mann, 2018). For investigation of the depression, corticosterone (CORT) is commonly used to induce chronic depression animals with disorders in HPA axis function with high levels of cortisol and glucocorticoids in blood plasm which are similar to the patients with depression (Malhi and Mann, 2018;Zhou et al, 2021;Oliveira et al, 2022). In our present study, we have successfully prepared the depression mice with CORT injection (i.p.…”
Section: Discussionmentioning
confidence: 99%